1990
DOI: 10.1007/bf01856504
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive monotherapy with tablet (Prompt-release) diltiazem: Multicenter controlled trials

Abstract: The tablet formulation of diltiazem has been available for the treatment of angina pectoris but has not been comprehensively evaluated in hypertension. This study's aim was to evaluate the efficacy, dose-response characteristics, and duration of action of tablet (prompt-release) diltiazem in mild to moderate hypertension. Three placebo-controlled trials were designed. The first (trial #1) evaluated the dose response of 120, 240, and 360 mg/day (q12h regimen) of diltiazem in parallel fixed-dose fashion using ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…This indicates that ionic cross-linking produced beads which were less rigid in structure and collapsed during drying, and may be ascribed to two reasons: less number of COOH groups introduced in the polymer chain by carboxymethylation (degree of substitution = 0.73) and inability of free Al 3+ ions to interact with the COOH groups. Unlike CaCl 2 , AlCl 3 ionizes in water to form hexaqua complex aluminum ion (AlCl 3 . Since free Al 3+ ions were not available in aqueous solution of AlCl 3 and charge on the aluminum complex ion was less, ionic cross-linking between the COOH groups and the aluminum complex ion was weak and produced less rigid hydrogel beads which collapsed during drying.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that ionic cross-linking produced beads which were less rigid in structure and collapsed during drying, and may be ascribed to two reasons: less number of COOH groups introduced in the polymer chain by carboxymethylation (degree of substitution = 0.73) and inability of free Al 3+ ions to interact with the COOH groups. Unlike CaCl 2 , AlCl 3 ionizes in water to form hexaqua complex aluminum ion (AlCl 3 . Since free Al 3+ ions were not available in aqueous solution of AlCl 3 and charge on the aluminum complex ion was less, ionic cross-linking between the COOH groups and the aluminum complex ion was weak and produced less rigid hydrogel beads which collapsed during drying.…”
Section: Resultsmentioning
confidence: 99%
“…Diltiazem-HCl, a calcium channel blocker is a popular and effective drug for adequate control of hypertension [3] and angina pectoris [4]. However, because of short half-life of 3.5 h, the drug is administered three to four times a day [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study (17) of diltiazem as monotherapy for the treatment of hypertension demonstrated that diltiazem immediaterelease tablets have good efficacy when taken three to four times a day.…”
Section: Discussionmentioning
confidence: 99%